How Amazon's e-commerce works? - Nicolò Maio; Beatrice Re (International Journal of Technology for Business (IJTB), 2020)
The following article will cover the phenomenon of Amazon and one of the keys to its success: the simplicity with which users can access to what they are interested in. The paper discusses the function of the algorithm now used by Amazon (A9). On the basis of the operation of the Amazon algorithm, the elements to focus on to increase sales on an e-commerce site are addressed. Through research and assessing material and consultation with multiple sources the paper analyses one of the biggest companies of our times, as well as a successful example of e-commerce: Amazon. In summary the paper examines how Amazon's platform manages to organize its vast marketing network with a click of a button. Furthermore, the paper focuses on the process that allows Amazon to understand what and how to sell, through an algorithm, giving tips and providing support to help both the seller who uses Amazon as an intermediary and customers.
Keywords: 650; Amazon; Algorithm; Ranking; E-commerce; SEO